Simulator-based human factors studies across 25 years the history of the halden man-machine laboratory - Skjerve, Ann Britt; Bye, Andreas (London Springer London, 2011)
The Halden Man-Machine Laboratory (HAMMLAB) has been at the heart of human factors research at the OECD Halden Reactor Project (HRP). The HRP is sponsored by a group of organizations representing nuclear power plant regulators, utilities, research institutions and vendors. The HRP is hosted by the Institute for Energy Technology (IFE) in Halden, Norway. HAMMLAB comprises three full-scale nuclear power plant control room research simulators. The simulator studies performed in HAMMLAB have traditionally been experimental in nature. In a simulator it is possible to study events as they unfold in real time, in a highly realistic operational environment under partially controlled conditions. This means that a wide range of human factors issues, which would be impossible or highly impracticable to study in real-life settings, can thus be addressed in HAMMLAB. Simulator-based Human Factors Studies Across 25 Years celebrates the twenty-fifth anniversary of HAMMLAB by reviewing the human factors studies performed in HAMMLAB across this time-span. A range of human factors issues have been addressed, including: human-system interfaces; alarm systems; computerized procedures; human-automation interaction; staffing and teamwork; and human reliability. The aim of HAMMLAB studies has always been the same: to generate knowledge for solving current and future challenges in nuclear power plant operation to contribute to safety. The outcomes of HAMMLAB studies have been used to support design and assessment of nuclear power plant control rooms.
1. The Use of Simulators in Human Factors Studies Within the Nuclear Industry -- 2. The History of HAMMLAB -- 3. The Purpose of HAMMLAB and the Theoretical Basis for Experimental Research -- 4. Methodological Challenges in HAMMLAB -- 5. Simulator Studies: The Next Best Thing? -- 6. Human Performance and Plant Safety Performance -- 7. More Than Forty Years of Operator-Process-Communication Research -- 8. Experiments with Conventional and Advanced Modes of Instrumentation in HAMMLAB -- 9. The Advanced Control Room Project ISACS -- 10. Alarm Systems -- 11. Information Display Design: Three Attempts at Superseding the Traditional Process Mimic Display -- 12. Staffing Levels: Methods for Assessing Requirements -- 13. Computerized Procedures -- 14. Can Human Operators and High-Level Automatic Systems Work Together? -- 15. Task Complexity - What Challenges the Crew and How Do They Cope? -- 16. International HRA Empirical Study, Overall Methodology and HAMMLAB Results -- 17. Work Practices and Cooperation in a Near Future and Far Future Operational Environment -- 18. Augmented and Virtual Reality Research in Halden 1998 - 2008 -- 19. Knowledge Transfer to Industry from HAMMLAB Related Research Activities -- 20. Human Performance Research and Its Uses to Inform Human Reliability Analysis -- 21. Studies for the Future.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Nuclear power plants -- Control rooms -- Human factors; Nuclear power plants -- Control rooms -- Human factors -- Simulation methods